2004
DOI: 10.1051/0004-6361:20035697
|View full text |Cite
|
Sign up to set email alerts
|

Properties of isolated disk galaxies

Abstract: Abstract. We present a new sample of northern isolated galaxies, which are defined by the physical criterion that they were not affected by other galaxies in their evolution during the last few Gyr. To find them we used the logarithmic ratio, f , between inner and tidal forces acting upon the candidate galaxy by a possible perturber. The analysis of the distribution of the f -values for the galaxies in the Coma cluster lead us to adopt the criterion f ≤ −4.5 for isolated galaxies. The candidates were chosen fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
108
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(117 citation statements)
references
References 23 publications
8
108
1
Order By: Relevance
“…This was confirmed by Elmegreen et al (1990) and Giuricin et al (1993), who both found that galaxies in binary systems are preferentially early type and barred. A similar result was reported by Varela et al (2004). Interestingly, while the fraction of barred disks in clusters or groups is not higher than in the field (Kumai et al 1986;van den Bergh 2002van den Bergh , 2007Marinova et al 2009), Thompson (1981) and Andersen (1996) presented evidence that barred galaxies in the Coma and Virgo clusters are more concentrated toward the cluster centers than unbarred disks.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…This was confirmed by Elmegreen et al (1990) and Giuricin et al (1993), who both found that galaxies in binary systems are preferentially early type and barred. A similar result was reported by Varela et al (2004). Interestingly, while the fraction of barred disks in clusters or groups is not higher than in the field (Kumai et al 1986;van den Bergh 2002van den Bergh , 2007Marinova et al 2009), Thompson (1981) and Andersen (1996) presented evidence that barred galaxies in the Coma and Virgo clusters are more concentrated toward the cluster centers than unbarred disks.…”
Section: Introductionsupporting
confidence: 75%
“…This finding indicates that bar formation, in general, is independent of environment, which was also found by van den Bergh (2002). On the other hand, Varela et al (2004) found twice as many bars in perturbed as in isolated galaxies. We investigate these results further in Sect.…”
Section: The Optical Bar Fraction and Its Dependence On Galaxy Propermentioning
confidence: 94%
See 1 more Smart Citation
“…In order to compare interaction probabilities, we calculate the perturbation parameter f for the galaxies in the Ursa Major cluster and the Virgo cluster. The f value is defined by Varela et al (2004) as f = log Fext Fint = 3log R Dp + 0.4(mG − mp),…”
Section: Environmental Effects In a Lower Density Clustermentioning
confidence: 99%
“…Even binary companions promote bar formation and may shift the galaxy to an earlier Hubble type because of torqued inflow (Elmegreen, Elmegreen, & Bellin 1990). Bars are also more common in perturbed galaxies (Varela et al 2004). Major mergers form ellipticals (Toomre & Toomre 1972;Schweizer 1998), and in the process, they form at least the youngest halo globular clusters (Ashman & Zepf 1992), and may produce counter-rotating cores (Kannappan & Fabricant 2001).…”
Section: Summary Of Evolutionary Effects Over a Hubble Timementioning
confidence: 99%